The Relationship between Television Watching Habits and Leisure Time: A Research on Ugandan Students in Turkey - Muyingo, Rajab Idd; Kirik, Ali Murat (International Journal of Cultural and Social Studies, 2018)
Media technologies have become actors in people's everyday life as they occupy a bigger portion of people’s leisure time for purposes of self-development and entertainment. Despite the invention of new media technologies of the Internet, smartphones, and computers, society still spends time in front of the screen watching television at a considerable rate. According to the World Youth Report (2003), young people in the developed world spend an average of about two hours daily in front of the television and their engagement in active leisure such as sports and the arts is also greater during their leisure time. This study had hypothesis that “Watching Television impacts on students’ leisure time activities”. The objective was; to examine how TV watching influence students’ leisure time activities. It also aimed at identifying students’ leisure time activities. This study used a random sampling technique to select respondents of Ugandan nationality studying in Turkey. Selected respondents were invited to answer a designed online questionnaire. A total of N=107 respondents from 8 cities in Turkey took part in the study. This study’ findings are summarized in frequencies and percentages. The study showed that on a daily basis the majority of the respondents 52.6% considered 3-4 hours as their leisure time for watching television. The results show that 74.5% of the respondents preferred watching Ugandan television channels during their leisure time whereas only 25.5%, watched Turkish television channels. It’s worth noting that 48.6% of the majority respondents agreed that watching television stimulates their academic learning. Meanwhile 36.4% of the participants in this study watched television during their leisure time for entertainment and pleasure purposes and 32.7% watched television for information and news purposes. In the same line 43% of the respondents agreed that television watching influences their leisure time activities like book reading, shopping behavior, touring among others.
Keywords: Leisure Time; Television Viewership; Students